PENGARUH EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BADUNG - Partini, I Gusti Ayu San Yogi; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023, 2023)
The purpose of this study was to determine the effect of hotel tax effectiveness, restaurant tax effectiveness, hotel tax contributions and restaurant tax contributions to the Regional Original Revenue of Badung Regency. The research sample consists of hotel tax revenue data and restaurant tax revenue data for three years (years 2018-2020). The analysis technique used are descriptive quantitative and multiple linear regression to test the relationship between the dependent variable and the independent variable, after previously all data met the requirements of the classical assumption test. The results of the analysis show that the effectiveness of the hotel tax has a positive effect on the PAD of the Badung district, the effectiveness of the restaurant tax has no affect on the PAD of the Badung district, the contribution of the hotel tax has a positive effect on the PAD of the Badung district, the concontribution of the restaurant tax has no affect on the PAD of the Badung district.